The Influence of Growth Opportunity, Profitability, and Financial Distress on the Company Value (IDX) - Maria Magdalena Kelu Balawanga; Sri Hermuningsih; Alfiatul Maulida (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Organizations that convert raw ingredients into semi-finished or finished commodities are known as food and beverage companies. The goal of this study is to look into and assess connected topics such as growth potential, profitability, financial distress, and company value. The research utiliutilizedsed second data in form of income statement from the Indonesia Stock Exchange (IDX). Purposive sampling was utilized to collect data for this investigation. The survey included 14 companies and 42 data points. The conclusions of Hypothesis (1) Growth potential influences the company's value, Hypothesis (2) Profitability has no effect on the company's value, and Hypothesis (3) Financial distress has no effect on the company's value were discovered. Hypothesis (4), on the other hand, asserts that the company's value is affected by growth opportunity, profitability, and financial crisis all at the same time. The worth of a company will increase if its profitability level is higher. The company's worth will improve if the level of financial distress is lowered. Keywords: Growth Potential, Profitability, And The Impact Of Financial Distress On The Company's Value